Polysiloxane-based scintillators as radiation sensors: state of the art and future perspectives - Carturan, Sara Maria; Moretto, Sandra; Quaranta, Alberto (Frontiers in Sensors, 2025)
Polysiloxane scintillators are emerging as promising radiation sensors due to their high radiation resistance, mechanical flexibility, chemical inertness, and thermal stability compared to traditional plastics. This mini-review traces the evolution of these materials from early formulations to current high-performance scintillators. Their capabilities for particle discrimination, thermal neutron detection, and real-time dose monitoring in proton radiation therapy are highlighted. The chemical versatility of polysiloxanes allows the optimization of energy transfer and light yield, outperforming commercial plastics. Recent developments have led to photocurable, 3D-printable polysiloxane scintillators, opening new avenues. Despite remarkable progress, much room remains for innovations by leveraging the chemistry of siloxane precursors. The entrance of polysiloxanes into the landscape of radiation detectors represents an opportunity to further expand the applications of polymer-based scintillators.